THE EFFECT OF SELF-EFFICACY AND PARENTAL SUPPORT ON SELF-REGULATED LEARNING (SRL) OF HIGH SCHOOL STUDENTS PRIVATE ASSISI SIANTAR - Ramot Hasugian; Hasanuddin; Yudistira Fauzy Indrawan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Self Regulated Learning is currently having many problems in implementing learning services. Self regulated learning is certainly influenced by many factors. This study aims to analyze and determine the influence of self-efficacy and parental support on self regulated learning. This study is included in quantitative research with an associative causal nature. The sample of this study was 122 students spread across Asisi Siantar Private High School. The research data were collected using a research scale that was declared valid and reliable. The data analysis technique used multiple linear regression analysis. The results of the study showed that (1)there is an influence of self-efficacy on self-regulated learning.From the results of the statistical analysis it was foundThe results of the hypothesis test found a coefficient value of rx1y of 0.685 with p < 0.05, and a predictor determinant coefficient value () of 0.469., this means that the high and low levels of self-efficacy arehaving children can increase or decrease self-regulated learning. (2)There is an influence of parental support on self-regulated learning. The results of the hypothesis test found a coefficient value of rx1y of 0.359 with p < 0.05, and a predictor determinant coefficient value () of 0.369., thus it can be concluded that the amount of parental support a child receives will increase or decrease self-regulated learning. (3)There is an influence of self-efficacy and parental support on self-regulated learning.The results of the hypothesis test found the F coefficient valuereg = 38.550 with p <0.05, and the correlation coefficient between X1, X2 and Y obtained results of = 0.644 with p <0.05 and determinant coefficient = 0.414, thus it can be concluded that self-efficacy and parental support together influence self-regulated learning, the contribution of both in increasing self-regulated learning is 41.4%. Thus it can be concluded that the third hypothesis is that there is a positive relationship between self-efficacy and parental support for self-regulated learning.